The Relative Impact of Different Types of Military Sexual Trauma on Long-Term PTSD, Depression, and Suicidality - Galovski, Tara E. (Journal of interpersonal violence, 2023)
Sexual assault and harassment in the U.S. military are very common. Military sexual trauma (MST) is defined as sexual assault or harassment experienced during military service; yet, the relative impact of sexual assault, harassment, and their combination is not well understood. Given the extent and potential severity of the long-term outcomes of MST, it is critical to evaluate the relative impacts of these types of MST on long-term mental health outcomes. Veterans (n = 2499; 54% female) completed self-report measures of experiences of sexual assault and harassment perpetrated by coworkers during military service, posttraumatic stress disorder (PTSD), depression, and suicidality. Controlling for combat exposure, all types of MST experiences (Harassment Only, Assault Only, or Both) compared to No MST predicted greater severity of PTSD, depression, and suicidality after military service. Compared to Veterans with No MST, those who experienced Both Assault and Harassment reported significantly more severe PTSD, depression, and suicidality followed by Harassment Only, and then Assault Only. Data suggest that different types of MST experiences have an impact on long-term mental health outcomes, and the combination of Both sexual Assault and Harassment is particularly deleterious.